Assessing the Effectiveness of Zero Tillage and Legume-based Cropping Systems for Enhancing Soil Nitrogen Concentrations and Stocks under Rainfed Pearl Millet Production Systems - A. Chaudhary; Mahesh C. Meena; R.S. Bana; A. Dey; S.P. Datta; D. Mahala; R. Mishra (Journal of the Indian Society of Soil Science, 2023)
Nitrogen (N) is a critical factor in determining the potential yield of crops, and agronomic practices play a crucial role in regulating the forms and availability of N in soils to the plant. Therefore, this study employed a split-plot design, where the main plots were allocated to four tillage methods: zero tillage with crop residue retention (ZT+R), zero tillage with crop residue removal (ZT-R), conventional tillage (CT), and undisturbed soils (UD). The sub-plots were designated for four cropping systems: pearl millet-chickpea (PM-C), pearl millet-chickpea-fodder pearl millet (PM-C-FPM), pearl millet-chickpea-mung bean (PM-CM), and the natural grasses in UD. The study aimed to understand the effects of different management practices on various forms of N in soil, including mineral-N, hot-water extractable organic N (HWEON), and available N (AvlN), as well as mineral N stock, HWEON stock, and total N stock in different soil layers. The study found that ZT+R significantly increased soil mineral N content and stock by 20% compared to CT across 0-30 cm soil depth. The effects of these practices on mineral-N concentrations were most pronounced in the surface soil layer. Furthermore, ZT practices and legume-based cropping systems enhanced N concentration and its availability. The study also revealed that HWEON content and its stocks were more sensitive to soil tillage practices than cropping systems, with ZT+R having 3.79 times higher HWEON concentration than CT at 0-5 cm soil depth. The significant differences for total N among tillage practices were more pronounced under ZT+R compared to CT. The research highlights the need for using conservation tillage practices, such as ZT+R, in combination with legume-based cropping systems to improve N availability and enhance soil fertility.